Meta Analisis Menggunakan Metode Mind Mapping dalam Meningkatkan Kemampuan Berpikir Kritis Siswa - M. Safri Sholahudin; Deni Adi Putra; Fajar Setiawan (Universitas PGRI Adi Buana Surabaya, 2021)
This study aims to determine the results of the analysis using the Mind mapping method to improve critical thinking skills in elementary schools, because in elementary schools students need to increase their potential for provision in everyday life by using the mind mapping method to improve thinking skills. critical. This research method uses descriptive analysis, this data collection technique uses meta-analysis research, namely research conducted by repetition and analyzing research from several previous research results. Data collection in this study was carried out by browsing journals on several electronic media. Data analysis of ten articles obtained an average of 60,098% results and 74,379% after results. Based on research data carried out by meta-analysis, it can be concluded that the application of the mind mapping method has been done by many researchers before, this method can improve students' critical thinking skills. After analyzing the ten articles above, it can be concluded that the students 'critical thinking skills increased by an average of 74.4 and the previous score with an average of 67.8. This was declared successful because of the increase in students' critical thinking. This is expected to be a reference for teachers so that they can use the mind mapping method in teaching and learning activities in education. The Mind mapping method is very effective for learning because the mind mapping method is proven to improve critical thinking and student learning outcomes for the better.